Selection following Gene Duplication Shapes Recent Genome Evolution in the Pea Aphid Acyrthosiphon pisum. (2nd May 2020) - Fernández, Rosa; Marcet-Houben, Marina; Legeai, Fabrice; Richard, Gautier; Robin, Stéphanie; Wucher, Valentin; Pegueroles, Cinta; Gabaldón, Toni; Tagu, Denis
Abstract: Ecology of insects is as wide as their diversity, which reflects their high capacity of adaptation in most of the environments of our planet. Aphids, with over 4, 000 species, have developed a series of adaptations including a high phenotypic plasticity and the ability to feed on the phloem sap of plants, which is enriched in sugars derived from photosynthesis. Recent analyses of aphid genomes have indicated a high level of shared ancestral gene duplications that might represent a basis for genetic innovation and broad adaptations. In addition, there are a large number of recent, species-specific gene duplications whose role in adaptation remains poorly understood. Here, we tested whether duplicates specific to the pea aphid Acyrthosiphon pisum are related to genomic innovation by combining comparative genomics, transcriptomics, and chromatin accessibility analyses. Consistent with large levels of neofunctionalization, we found that most of the recent pairs of gene duplicates evolved asymmetrically, showing divergent patterns of positive selection and gene expression. Genes under selection involved a plethora of biological functions, suggesting that neofunctionalization and tissue specificity, among other evolutionary mechanisms, have orchestrated the evolution of recent paralogs in the pea aphid and may have facilitated host–symbiont cooperation. Our comprehensive phylogenomics analysis allowed us to tackle the history of duplicated genes to pave the road toward understanding the role of gene duplication in ecological adaptation.